Numbed! - Lubar, David (Minneapolis : Millbrook Press, 2013)
When a robot at the math museum zaps their math skills, sixth-grader Logan and his mischievous friend, Benedict, must pass a series of math challenges to retrieve their knowledge.
Keywords: Mathematics -- Fiction; Mathematics -- Juvenile fiction